A study to determine the knowledge, attitude and practice of doctors and nurses on the role of physiotherapy in management of respiratory conditions: pulmonary tuberculosis, pneumonia and asthma at University Teaching Hospital - Kapesa, Beatrice (Lusaka: University of Zambia , School of Medicine, 2013)
Tuberculosis is one of the major causes of disabilty and death world wide. Pnuemonia is the largest single killer of children around the world, responsible for deaths of morre than 2 million children the age of five every year, accounting for almost one in five under five deaths world wide. Physiotherapists have a role in the management of a wide spctrum of RCs in primary and secondary care. The purpose of this study was to assess the level of knowledge, attitudes and practices of doctors and nurses on the role of physiotherapy in management of RCs.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Physiotherapy.
Includes bibliographical references.
Keywords: Physical Therapy Modalities; Treatment Outcome; Respiratory organs--Diseases.